Realizing High Performance in Flexible Mg3Sb2−xBix Thin‐Film Thermoelectrics - Boxuan Hu; Xiao‐Lei Shi; Tianyi Cao; Min Zhang; Wenyi Chen; Siqi Liu; Meng Li; Weidi Liu; Zhi‐Gang Chen (Advanced Science)
Abstract As advancements in Mg‐based thermoelectric materials continue, increasing attention is directed toward enhancing the thermoelectric performance of Mg3Sb2 and its integration into thermoelectric devices. However, research on Mg3Sb2 thin films and their application in flexible devices remains limited, leaving ample room for improvements in fabrication techniques and thermoelectric properties. To address these gaps, this study employs magnetron sputtering combined with ex‐situ annealing to dope Bi into Mg3Sb2 thin films, partially substituting Sb. This approach enhances the near‐room‐temperature performance and plasticity, yielding high‐performance Mg3Sb2−xBix thermoelectric thin films. The films achieve a power factor of 3.77 µW cm−1 K−2 at 500 K, the highest value reported for p‐type Mg3Sb2 thin films to date. Comprehensive characterization demonstrates precise thickness control, strong adhesion to various substrates, and excellent flexibility, with performance degradation of less than 12% after 1000 bending cycles at a radius of 5 mm. Additionally, a flexible thermoelectric device is constructed using p‐type Mg3Sb1.1Bi0.9 and n‐type Ag2Se legs, achieving an output power of 9.96 nW and a power density of 77.38 µW cm−2 under a temperature difference of 10 K. These findings underscore the potential of these devices for practical applications in wearable electronics.